A simple and static preservation system for shipping retinal pigment epithelium cell sheets. (20th February 2019) - Hori, Kanji; Kuwabara, Junichi; Tanaka, Yuji; Nishida, Mitsuhiro; Koide, Naoshi; Takahashi, Masayo
Abstract: The ability to move cells and tissues from bench to bedside is an essential aspect of regenerative medicine. In this study, we propose a simple and static shipping system to deliver tissue‐engineered cell sheets. Notably, this system is electronic‐device‐free and simplified to minimize the number of packing and opening steps involved. Shipping conditions were optimized, and application and verification of the system were performed using human iPS cell‐derived or fetal retinal pigment epithelium (RPE) cell sheets. The temperature of the compartments within the insulated container was stable at various conditions, and filling up the cell vessel with medium effectively prevented turbulence‐induced mechanical damage to the RPE cell sheets. Furthermore, no abnormal changes were observed in RPE morphology, transepithelial electrical resistance, or mRNA expression after transit by train and car. Taken together, our simple shipping system has the potential to minimize the costs and human error associated with bench to bedside tissue transfer. This specially designed regenerative tissue shipping system, validated for use in this field, can be used without any special training. This study provides a procedure for easily sharing engineered tissues with the goal of promoting collaboration between laboratories and hospitals and enhancing patient care.